The Intangibles of Leadership : the 10 Qualities of Superior Executive Performance - Davis, Richard A. (J. Wiley & Sons Canada, 2010)
It's the Subtleties that Matter!. What is the real difference between competent leader and extraordinary executive? Is it pedigree, experience, intelligence? The answer is yes ... and much more. Exceptional leadership hinges on a complex interaction between individual psychology and unique business needs. At the top rung of the ladder, where the dynamics are most complicated, subtle adjustments in style can produce outstanding results. In his new book, The Intangibles of Leadership, Management Psychologist Richard Davis, Ph. D., uncovers patterns in the attributes that truly distinguish those wh.